Why is low body fat rarely seen in large‐sized male athletes?. Issue 6 (5th February 2020) - Abe, Takashi; Bell, Zachary W.; Wong, Vickie; Spitz, Robert W.; Loenneke, Jeremy P.
Abstract: Objectives: It is unknown why low body fat is rarely seen in large‐sized athletes (>100 kg body mass). The aim of this review was to examine the relationship between body mass and body composition (fat mass and fat‐free mass) in elite male athletes, and to discuss the possible reasons why low body fat is rarely seen in large‐sized male athletes. Methods: A search using two electronic databases was conducted. Eighteen studies estimated body composition in elite athletes by dual‐energy X‐ray absorptiometry, totaling 2249 elite male athletes and 72 data points. Results: Our results indicated that low body fat (eg, less than 10% body fat) was rarely seen in large‐sized male athletes over 100 kg body mass. The larger the body mass, the higher the fat‐free mass, with fat‐free mass leveling off when body mass exceeds approximately 120 kg. Conclusion: Possible reasons for this are unknown but we provide some ideas for why this might occur. The two different stages to consider with respect to skeletal muscle growth: the amount of growth during development and the amount of growth as a result of long‐term resistance training. In certain sporting events, a large body mass may be favored. However, the large‐sized athletes have to balance any potential positive influence of body mass on sports performance with the potential negative factors associated with body fat accumulation. Further research is warranted, as there is currently limited evidence on this topic.